FOSTERING MODERATION THROUGH EDUCATION: CHALLENGES AND OPPORTUNITIES IN A MULTICULTURAL SOCIETY - Giman Bagus Pangeran; Siti Annisah; Aria Septi Anggaira (CV. TOTUS TUUS, 2025)
Tulang Bawang Regency, located in Lampung Province, Indonesia, represents a multicultural society marked by ethnic, religious, and socio-cultural diversity. This diversity, while enriching, also brings challenges such as social inequality, conflicting identities, and differing interpretations of moderation values. This study aims to explore the implementation of moderation values in fostering social harmony within this complex environment. A qualitative case study approach was employed, involving in-depth interviews, participatory observation, and document analysis. Fifteen key informants—including religious leaders, traditional figures, and community activists—were purposively selected. Data were analyzed using Braun and Clarke’s thematic analysis framework. The findings reveal that challenges in implementing moderation stem from contrasting views about its meaning, external disruptions (such as social media), economic disparities, and insufficient political consistency. Nonetheless, significant opportunities exist, including interfaith education, the proactive role of traditional leaders, youth engagement, and civil society initiatives. Educational programs and strong leadership were found essential to shaping early tolerance. This study concludes that the consistent promotion of moderation values requires an integrated approach involving inclusive education, equitable policies, media literacy, and the active participation of all societal elements. The research offers valuable insights for policymakers and educators aiming to strengthen social integration in multicultural settings. Future research is recommended to evaluate the long-term impact of moderation-based policies and to explore comparative studies in other culturally diverse regions.